Spiritual Experience: Scientific, Philosophical, and Theological Implications - Chatlos, John Calvin (Zygon, 2025)
A review of spiritual experience centered on a framework of spirituality developed by the author identifies implications for the disciplines of science, philosophy, and theology, presenting specific questions to be considered. A general introduction clarifies the terms and limits of the discussion and the focus of the requested commentary prepared for the Institute on Religion in an Age of Science Conference in June 2025. Scientific focus includes the dual process of cognition and its implications for medicine, psychology, psychiatry, neuroscience, anthropology and evolution, and the inclusion of “soul studies.” Philosophical discussion highlights the values, Ground of Being, and universal moral values challenging the naturalistic fallacy of “is-ought.” Theological implications focus on the Veil of Illusion, mystical experience, transcendence versus immanence, the causal joint problem, a specific Faith Process and a proposed field of applied spirituality, and the nature of soul. A common discussion for all disciplines is the role of ontology and a worldview that demands disciplinary agreement.